My worst nightmare [videorecording (DVD)] = Mon pire cauchemar - Fontaine, Anne; Huppert, Isabelle; Poelvoorde, Benoît; Dussollier, André (Strand Releasing, 2012)
Agathe is an uptight, impatient art dealer who lives in an expensive Parisian apartment with her wealthy publisher husband. Patrick is a skirt-chasing, unemployed single father who lives in a van with his son. Their lives would never intersect except that their two sons are best friends and her husband has hired Patrick to remodel their apartment. Hilarity ensues as this odd couple relationship turns into Agathe's worst nightmare.